MAKNA TEKSTUAL DAN INTERPERSONAL PIDATO BILL GATES: UNIVERSITAS HARVARD (2007) MENURUT TEORI METADISCOURSE HYLAND - Intan Mustika Sari (Haluan Sastra Budaya, 2020)
This study aims to analyze the interpersonal and textual meanings conveyed by Bill Gates at the graduation of Harvard University students in 2007 by using the metadiscourse theory introduced by Hyland. By analyzing the interactional and interactive sources found in the speech, the interpersonal and textual meanings can be revealed. The data were collected and selected from the text of Bill Gates' speech at the graduation of Harvard university students in 2007 which was retrieved from news.harvard.edu. The steps of analyzing data include describing the elements of linguistic data, calculating the percentage of interactive and interactional sources found in the speech, then analyzing the data to reveal the interpersonal and textual meanings. The results show that there are 74.6% interactive resources and 25.4% interactional resources found in Bill Gates' speech. Among these resources, the transitions of interactive resources are in the first place with a percentage of 63,7%. It indicates that Bill Gates was very good at organizing texts, making text clear and coherent for his audience, so that it became easier for them to find connections between arguments and better understand about what he was saying.